1985
DOI: 10.1017/s0317167100047144
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Intracerebral Haemorrhage: An Analysis of Factors Affecting Prognosis

Abstract: ABSTRACT:A retrospective study of 100 patients with spontaneous intracerebral haemorrhage was carried out, to identify clinical factors which have a predictive value for outcome. Numerical equivalents for the admission level of consciousness (the Glasgow Coma Scale), ventricular rupture, partial pressure of oxygen in the blood, the electrocardiogram, clot location, and clot size were combined into equations predicting outcome. The best single parameter for prediction was the Glasgow Coma Scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
3

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 22 publications
2
22
0
3
Order By: Relevance
“…In particular, level of consciousness on admission has been reported to be one of the most important independent predictors of 30-day 36) , 1-year 31) , and all in hospital mortalities 4) . Other studies 12,40) have used GCS to assess level of consciousness. In the present study, we found a similar relation between GCS and level of consciousness graded simply as conscious or unconscious, as described in the RLS 11,37) .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, level of consciousness on admission has been reported to be one of the most important independent predictors of 30-day 36) , 1-year 31) , and all in hospital mortalities 4) . Other studies 12,40) have used GCS to assess level of consciousness. In the present study, we found a similar relation between GCS and level of consciousness graded simply as conscious or unconscious, as described in the RLS 11,37) .…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous ICH accounts for 4% to 15% of cases of acute stroke but is the most fatal form of this disease. [1][2][3][4][5][6] Warfarin use increases both the risk of developing ICH [7][8][9][10] and its mortality. 1,11 The effect of warfarin on ICH severity appears to be related to an increased risk of continued in-hospital bleeding.…”
mentioning
confidence: 99%
“…25,26 The prognosis for patients with RPCH was worse than for those with nonrecurrent bleeding. Only 27% of patients had good functional recovery compared with 37% to 55% of patients with a first cerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%